Characteristics of the capture threads of Synotaxus sp. (probably S. turbinatus) webs (Araneae, Synotaxidae) - Barrantes Montero, Gilbert (2009)
Synotaxus spiders have independently evolved aerial, planar webs to intercept and retain prey, but these webs differ in several respects from planar araneoid webs with similar functions. The silk capture threads of Synotaxus sp. (probably S. turbinatus Simon, 1895) webs differ markedly from the spirally arranged capture threads in araneoid webs. The sticky globules on the capture threads of Synotaxus sp. webs are widely spaced, and the threads are spring-like and apparently unique within spiders. This arrangement appar- ently allows a great extensibility, as the spring-like form is straightened under high tension, but coils again when the tension decreases. Some aspects of the feeding behaviour and habitat use of Synotaxus sp. are also described.